Wątki arystotelesowskie w psychologii i filozofii umysłu Franza Brentano - Kamińska, Sonia (Filozofia Nauki, 2016)
This paper revolves around some crucial Aristotelian traces in Franz Brentano's philosophy of mind and psychology. I describe the distinction between the intellectual soul understood, on the one hand, as a substratum for mental phenomena and, on the other, as a "stream" or "bundle" of mental phenomena. I take into consideration Brentano's opus magnum, Psychology from an Empirical Standpoint as well as his Aristotelica series. I translate into Polish and analyse his notes for the unpublished parts of Psychology (Ps 62/54011-54012, Ps 50/52143-147) and give an account of what some Brentanian (Rollinger) and Aristotelian (Macfarlane and Polansky) scholars have to say about the ontological status of the intellectual soul.